Konsep Nabi dan Rasul dari Perspektif Al-Qur'an - Wan Ali, Wan Zailan Kamaruddin (Jurnal Usuluddin, 1997)
The words Nabi (Prophet) and Rasul (Messenger) are often mentioned in the Holy Qur'an. Both have their own significant role and influence in Islam. Therefore, this article aims to discuss the definitions of the terms of Nabi and Rasul from the view points of the Holy Qur'an and also to show the comparison between them.